Hydration does not prevent orthostatic hypercoagulability - Masoud, Muhannad; Sarig, Galit; Brenner, Benjamin; Jacob, Giris (Thrombosis and Haemostasis, 2010)
Prolonged standing activates the coagulation cascade by the activation of endothelial cells, and probably the haemoconcentration effect contributes to this "orthostatic hypercoagulability". It was the objective of this study to assess whether rehydration (haemodilution) prevents or attenuates orthostatic induced thrombin formation. Twelve healthy young subjects were studied during two separate visits. Haematocrit (Hct), total plasma protein, coagulation profile tests, including endothelial activation related factors, and protein C global pathway were studied at rest supine, and while standing at 15 and 30 minutes (min). During the second visit the study was repeated after intravenous 1.5 liter 0.9% saline. While in supine posture, intravenous rehydration resulted in Hct reduction of 14.2 ± 2% (haemodilution), a decrease of 11.5 ± 1.3% in total protein, as well as a significant dilutional effect on most of the coagulation parameters. Still standing for 30 min, with and without rehydration caused a comparable increase in tissue factor by 49.83 ± 13.6%, and 35.34 ± 8.55% (p>0.05), respectively and in von Willebrand factor (vWF) 9.5 ± 2.4% and 13.59 ± 2.17% (p>0.05), respectively. At 30 min standing, after intravenous rehydration, factor V and VIII activities, and fibrinogen rose by 22 ± 1.9%, 31.2 ± 6.2%, 9.15 ± 2.64%, (p<0.002 for all), respectively. Prothrombin fragments 1+2 elevated by 84.84 ± 15.3% (p<0.001). Comparable results were obtained with and without the rehydration. Additionally, protein C assay results decreased by 19.4 ±1.7% and 17.5 ± 2.6%, with and without fluids (p<0.05 for both). In healthy subjects, intravenous prophylactic rehydration with normal saline resulted in a haemodilution of all the coagulation parameters, but did neither attenuate nor prevent the orthostatic hypercoagulability.
Keywords: Orthostatic hypercoagulability; prolonged standing; tissue factor; hydration